2019
DOI: 10.1186/s12944-019-1162-9
|View full text |Cite
|
Sign up to set email alerts
|

The differential effects of fatty acids on enterocytic abundance of amyloid-beta

Abstract: BackgroundConsumption of a Western-styled diet enriched in saturated fatty acids (SFA) relative to polyunsaturated fatty acids is positively associated with risk for Alzheimer’s disease. Whilst potential causal mechanism are unclear, there is increasing evidence that chronic ingestion of SFA enriched diets promote increase the plasma levels of lipoprotein-associated amyloid-β (Aβ). However, the effects of dietary mono- and poly-unsaturated fats (MUFA/PUFA) on nascent lipoprotein Aβ abundance have not been prev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 23 publications
1
19
0
Order By: Relevance
“…The Gram-negative bacteria are the main producers of Aβ prion-like proteins (i.e., a-synuclein) and lipopolysaccharides (LPS), and select pro-inflammatory TLR4. Among the Gram-negative bacteria, B. subtilis and E. choli produce large amounts of Aβ and LPS [8,14,16,17].…”
Section: The Microbiota-gut As a Unique Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The Gram-negative bacteria are the main producers of Aβ prion-like proteins (i.e., a-synuclein) and lipopolysaccharides (LPS), and select pro-inflammatory TLR4. Among the Gram-negative bacteria, B. subtilis and E. choli produce large amounts of Aβ and LPS [8,14,16,17].…”
Section: The Microbiota-gut As a Unique Systemmentioning
confidence: 99%
“…Several studies have shown that, besides the brain, the microbiota-gut system is a site of Aβ production, and that the enterocytes contain substantial amounts of Aβ [40,48,49], and that diet and intestinal microbiota regulate the Aβ presence in the gut epithelium [17,25]. Gramnegative bacteria are a significant source of Aβ and of LPS, and the increased levels of these molecules found in AD brain plaques were related to dysbiosis.…”
Section: The Origin Of Amyloid Betamentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on the relationship between food and health focus on specific nutrients, for instance on saturated and unsaturated fat, fibers, etc. [28]. The latter could well be surrogate markers of nutritional diversity.…”
Section: Plos Onementioning
confidence: 99%
“…Pharmacological reduction of Aβ levels in the blood of wild-type mice by peripheral administration of a drug impermeable to the blood–brain barrier was linked to reduced Aβ levels in the brain [ 9 ]. Dietary fatty acids can also modulate plasma Aβ levels in wild-type mice [ 10 ]. These findings provide evidence that Aβ levels in blood can be modulated; however, further studies are needed to establish whether or not peripherally targeted strategies to reduce Aβ would be beneficial for brain function and cognition in the context of Alzheimer disease.…”
mentioning
confidence: 99%